KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN BANK SYARIAH - Erni Susana (Jurnal Keuangan dan Perbankan, 2009)
Individual characteristic and working environment would effect the achievement, while theindividual working achievement was the basic of organization working achievement. Managementneeded to pay attention on the individual characteristic and saw the working environment whichwas safe and promising organization so that employees or individual could work well in supportingemployees working achievement. The objective of this research was to prove the effect of individualcharacteristic and working environment to the employees working achievement. The method usedwas double regession analysis. The result showed that F test was 66,147 while Sig. = 0,000 = 0,05. Itmeant that individual characteristic variable and working simultaneously had signifi cant effect to thevariable of employees working achievement. The determinant coeffi cient result was 0,831. It meantthe effect of individual characteristic and working environment to the employees working achievementwas 0,831 or 83,1% while the rest was 0,169 or 16,9%. It was infl uenced by another variableout of the examined variable.